ANALISA PERILAKU KONSUMEN DALAM PENGGUNAAN E-MONEY (STUDI KASUS DUTAMALL BANJARMASIN) - Sholikhah, Sholikhah; Suarniki, Ni Nyoman; Pratiwi, Lusiana (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2023)
Abstract, The aim of this research is to analyze consumer behavior in using e-money (case study of Dutamall Banjarmasin). The reality shows that there are still few people who understand about e-money, there is still a lack of public thinking about e-money, there are still limited places that accept payments using e-money, and there is consumer behavior that influenced by the characteristics of cultural, social, personal and psychological factors The method used is a quantitative research method. The research population is an unlimited population and the sample in this study is a convenience sample. The research results show that cultural factors in the use of e-money at Dutamall Banjarmasin are considered not good. Social factors in using e-money at Dutamall Banjarmasin are considered good. Personal factors in using e-money at Dutamall Banjarmasin are quite good. Psychological factors in using e-money at Dutamall Banjarmasin are quite good.